TIDCO's achievements under the first Executive Director - Ifill, Kirk ([s.n.] [S.l.], 1996)
Highlights TIDCO's achievement which includes setting up the infrastructure of a worldwide marketing network for Trinidad and Tobago to drive promotion in tourism, trade and industry, and development work in new areas such as informatics; entertainment; international banking; handicraft and gift items etc.